KETERLIBATAN ORANG TUA DALAM PEMBELAJARAN ANAK USIA DINI SELAMA BELAJAR DARI RUMAH DI MASA PANDEMI COVID-19 - Jane Gresia Akollo; Meike Elsa Toisuta (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2020)
AbstrackIn children learning process that is conducted from home during the Covid-19 pandemic, parents must function as â€œteachersâ€.Â  As the 'teachers', parents must prepare themselves, starting from reading books, participating in webinars, following learning videos or videos of children's creativity activities in order to nourish their intellectuals with various information and knowledge.Â  This study employs a qualitative approach with a case study method on 10 parents (father or mother) who had early childhood (5-6 years) at PAUD Rafflesia Arnolis, Kayu Tiga, Soya Village Ambon City. The data were obtained through interviews and documentation. The result of this study reveal some foms of parental involvement namely there is a communication between parents and teacher, accompany and help children learn as well as privide learning facilities. In addition, there are several positive things created between parents and children, such as the closeness of parents and children, parents can follow and know about children's learning development and parents are enriched intellectually and creatively while being 'teachers' for children at home. The benefit of the research is that the parents realize how important it is for them to be involved in their childrens' learning process and recognize the forms of involvement. Thus, parents can improve the quality and intensity of their children's learning involvement at home during the Covid-19 pandemic.Keywords: parental involvement, early childhood, learning from home